2017
DOI: 10.3390/foods6090073
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of the Essential Oil of Fennel (Foeniculum vulgare) from Tajikistan

Abstract: The essential oil of fennel (Foeniculum vulgare) is rich in lipophilic secondary metabolites, which can easily cross cell membranes by free diffusion. Several constituents of the oil carry reactive carbonyl groups in their ring structures. Carbonyl groups can react with amino groups of amino acid residues in proteins or in nucleotides of DNA to form Schiff’s bases. Fennel essential oil is rich in anise aldehyde, which should interfere with molecular targets in cells. The aim of the present study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…5TVI is selected as the best template based on BLASTp result; it is 59.34% identical and 74% similar to fennel nsLTP1 with 100% query coverage and e-value of 3E−33. The homology modeling, therefore, indicated that the structure of fennel nsLTP1 has four α-helices: H1 (4-20), H2 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), H3 (42-57) and H4 (64-74); a long C-terminal tail (75-91); and three short loops at the positions of (21-25), (37-41), (58)(59)(60)(61)(62)(63) residues. The study from the crystal structure of 5TVI depicted that these helices are engaged in the form of a hydrophobic cavity, where the overall structure is stabilized by the presence of four disulfide bonds that exist between cysteine (4-51), (14-28), and ) that are also retained by fennel nsLTP1 structure 16 .…”
Section: Discussionmentioning
confidence: 99%
“…5TVI is selected as the best template based on BLASTp result; it is 59.34% identical and 74% similar to fennel nsLTP1 with 100% query coverage and e-value of 3E−33. The homology modeling, therefore, indicated that the structure of fennel nsLTP1 has four α-helices: H1 (4-20), H2 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), H3 (42-57) and H4 (64-74); a long C-terminal tail (75-91); and three short loops at the positions of (21-25), (37-41), (58)(59)(60)(61)(62)(63) residues. The study from the crystal structure of 5TVI depicted that these helices are engaged in the form of a hydrophobic cavity, where the overall structure is stabilized by the presence of four disulfide bonds that exist between cysteine (4-51), (14-28), and ) that are also retained by fennel nsLTP1 structure 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Fennel seed methanolic extract (FSME) was found to exert remarkable anticancer potential in human MCF-7 and HepG-2 cell lines by reducing the oxidative stress (Mohamad et al, 2011). Essential oil of fennel, rich in anise aldehyde shows hepatoprotective activity (Sharopov et al, 2017). Cyclophosphamide thus protecting the liver from toxicity and also from carcinogenicity caused by Cyclophosphamide (Sheweita et al, 2016).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Fennel seed methanolic extract (FSME) was found to exert remarkable anticancer potential in human MCF‐7 and HepG‐2 cell lines by reducing the oxidative stress (Mohamad et al., 2011). Essential oil of fennel, rich in anise aldehyde shows hepatoprotective activity (Sharopov et al, 2017).…”
Section: Studies On Cancer With Spices—major Bioactive Compoundsmentioning
confidence: 99%
“…Moreover, fennel essential oil is rich in aldehyde content, which interferes with molecular targets in cells and causes a low cytotoxicity. Sharopov et al (2017) summarized that the fennel essential oil exhibited potent cytotoxic activity against human cervical cancer, colorectal adenocarcinoma, breast adenocarcinoma, T lymphoblast leukemia, and adriamycin-resistant leukemia cancer cell lines. Furthermore, fenugreek also exerted anticancer effects due to its bioactive constituents such as saponins and flavonoids.…”
Section: Surh 1999mentioning
confidence: 99%